Game and preferences analysis for virtual water strategy based on a Hotelling model. (24th September 2021) - Zhi, Yuan; Hamilton, Paul B.; Yang, Hao; Sun, Yuanyuan; Wu, Guoyong; Liang, Longyue; Xiong, Debin
Abstract: The implementation of the virtual water strategy (VWS) transporting invisible water resources through product scheduling faces resistance due to limited reporting and understanding and the lack of motivation analysis for stakeholders. This study builds a semi‐quantitative Hotelling game model under different scenarios to analyse the influence of preference and material benefits on potential acceptance of VWS with policymakers and stakeholders. Equilibrium analyses of the game show that human preference can be as important as real benefits. With preference differences, it is hard to make all stakeholders accept or reject a VWS approach in achieving optimal results for environment and social welfare. To implement a sustainable VWS mode, modifying preferences through propaganda and education can be effective. The natural play of the game with modified preferences will ultimately favour a holistic VWS approach to responsible management. This model supports the effectiveness of game theory in the implementation of a VWS.